Once-daily, oral levofloxacin monotherapy for low-risk neutropenic fever in cancer patients. Issue 3 (March 2015) - He, Lixian; Zhou, Caicun; Zhao, Su; Weng, Heng; Yang, Guowang
<x xml:space="preserve">Abstract</x> This pilot study assesses the safety and efficacy of once-daily, oral levofloxacin monotherapy in Chinese patients with low-risk febrile neutropenia. In this prospective, single-arm, open-label, multicenter clinical trial, 46 adult Chinese patients with solid tumors and low-risk febrile neutropenia were included. Patients received oral levofloxacin monotherapy (500 mg orally/day) until day 12, followed by 7 days of follow-up (day 19). Body temperature was measured three times per day. On days 2, 3, 5–7, 9, 12, and 19, disease symptoms and vital signs were recorded, adverse drug reactions were assessed, and blood samples were collected to determine the whole-blood cell count and the absolute neutrophil count. Blood cultures and chest radiographs were performed simultaneously until negative results were found. Oral levofloxacin was effective and well tolerated in 97.6% of patients irrespective of the cancer type and cause of fever. Body temperature began to decline in 24.4, 68.3, and 90.2% of patients, respectively, at 12, 24, and 48 h after initiating levofloxacin therapy. On days 5 and 7, 95.1 and 97.6% of the patients had complete defervescence, respectively. The median time for absolute neutrophil count recovery to at least 1500/mm3 after initiation of treatment was 3 days. Only one patient reported mild diarrhea. This pilot study showed that oral levofloxacin quickly and effectively reduced fever, initiated neutrophil recovery, and was well tolerated in Chinese low-risk febrile neutropenic patients with solid tumors. Further study is needed to compare patient data of levofloxacin with the standard amoxicillin/ciprofloxacin protocol in this population for both safety and efficacy.